A Comparative Study of Enrollment Status and Academic Achievement of Government and Private Schools Students at Elementary Level: A Comparison of Enrollment and Academic Performance in Government and Private Elementary Schools in Haryana (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The present study was conducted in three district of Haryana state. The researcher tried to find out the enrollment status and academic achievement of government and private school’s students at elementary level in Haryana. The sample size is 30 government and private schools. Tool used are the school information blank, academic achievement score obtained from the school record. The data was analyzed by percentage method. The academic achievement of private schools students was found high than the government school’s students and enrollment status of private schools were better than the government schools.